Fluctuating Identities in Cyberspace and Cyberfeminism: A Comparison of Philippine and Korean Experiences - Ham, Jongsuk (Review of Women's Studies; Vol 20 No 1-2 (2010): Review of Women's Studies Volume XX, Numbers 1-2 (January-December 2010), 2011)
This essay provides a critical take on a Massive Multiplayer Online Role Playing Game (MMORPG) as an example of a cyberspace activity and applies empirical studies on online game players and feminist theories like Haraway's postulation of the cyborg and Braidotti's nomadic subject to see if Sadie Plant's expectation regarding cyberspace is feasible. It looks at the results of the survey answered by Philippine and (South) Korean players to see how the theories and reality match when comparing two different cultures.